Biodiversity, bioactivity, and chemical profile of endophytic fungi isolated from cashew (Anacardium occidentale) - DEWI NOVIANTI; ELFITA ELFITA; HARY WIDJAJANTI; SALNI SALNI; ELIZA ELIZA; RIAN OKTIANSYAH (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Novianti D, Elfita, Widjajanti H, Salni, Eliza, Oktiansyah R. 2025. Biodiversity, bioactivity, and chemical profile of endophytic fungi isolated from cashew (Anacardium occidentale). Biodiversitas 26: 2959-2969. Anacardium occidentale, called cashew, is used extensively in agriculture and medicine. Traditional medicine has extensively used the plant’s root barks, leaves, fruits, and seeds to cure various illnesses, including gastrointestinal issues, infections, and inflammation. Numerous reports have identified secondary metabolites that contribute to the biological activity of A. occidentale plants. The symbiotic endophytic fungi that inhabit the plant parts of A. occidentale may also generate bioactive substances that could be used as a source of medicine. This study examines the endophytic fungi associated with A. occidentale root barks, fruits, and seeds and their chemical profiles and bioactivity. Fresh tissue from root barks, fruits, and seeds was used to isolate endophytic fungi and identify them morphologically. The disk diffusion method was used to evaluate endophytic fungal extracts for antibacterial activity, while the DPPH method was used to test for antioxidant activity. Each endophytic fungal isolate's antibacterial and antioxidant activity was compared to the activity of the host plant. Endophytic fungal extracts with the same morphological characteristics in each plant part were subjected to GC-MS analysis to determine their chemical profiles. Sixteen endophytic fungal isolates were successfully isolated, including 8 isolates from root barks (RM1-RM8), 2 isolates from fruits (FM1-FM2), and 4 isolates from seeds (SM1-SM4). It shows that the highest number of endophytic fungi was found in the root bark, followed by the seed and fruit. The bioactivity of endophytic fungi in each organ is the same as that of its plant part. The results of morphological identification show that Aspergillus niger was found in all plant parts, namely in the root bark (RM7), fruit (FM1), and seeds (SM4). The antibacterial and antioxidant activities of A. niger isolates from the three different plant parts were varied. The results of the GC-MS analysis show that the endophytic fungal extract of A. niger in each plant part also has varying chemical profiles. The findings of this study can be used as information for drug development.